Pharmacists and pharmacy services in COVID-19 literature: A bibliometirc analysis - Abrar K. Thabit; Wajd S. Alsulmi; Nourah M. Aljereb; Omnia M. Khojah; Khadeja O. Almehdar; Manuel Jesús Cobo; Jimmy Jose; Antonio Vélez-Estévez (Elsevier, 2023)
Background: The COVID-19 pandemic had an enormous impact on the global economy and healthcare. Pharmacists were vital members of the healthcare system, and they participated in various strategies to reduce the effect of the pandemic. Numerous papers were published discussing their roles during the pandemic. Bibliometric analysis was used to measure the impact of publications on this topic and assessed them qualitatively and quantitatively over a specific time. Objective: Evaluate published literature pertaining to the roles of pharmacists and pharmacy services during the pandemic and identify gaps. Methods: An electronic search was conducted on PubMed database using a specific query. Eligible publications were published in English between January 2020 and January 2022 and discussed the role of pharmacists, pharmacies, and pharmacy departments during the pandemic. Clinical trials, studies on pharmacy education/training, and conference abstracts were excluded. Results: Of 954 records retrieved, 338 (35.4%) from 67 countries were included. Most papers (n = 113; 33.4%) were from the community pharmacy sector, followed by the clinical pharmacy sector (n = 89; 26.3%). Sixty-one (18%) papers were multinational, mostly involving two countries. The average number of citations of the included papers was 6 times (range 0-89). The most common MeSH terms were 'humans', 'hospitals', and 'telemedicine', where the former frequently co-appeared with the terms 'COVID-19' and 'pharmacists.' Conclusions: Results from this study illustrate the innovative and proactive strategies developed by pharmacists during the pandemic. Pharmacists from around the world are encouraged to share their experiences for stronger healthcare systems to counter future pandemics and environmental disasters.